PENGARUH MEDIA PEMBELAJARAN MACROFLASH 8 TERHADAP HASIL BELAJAR SISWA DITINJAU DARI MOTIVASI SISWA PADA PEMBELAJARAN TEMATIK TEMA 7 KELAS IV SD N MRANGGEN 01 - Ningsih, Puspa Evi Ratna Kumala; Purnomo, Joko; Reffiane, Fine (KALAM CENDEKIA PGSD KEBUMEN, 2018)
AbstractThis type of research is quantitative research with Quasi Experimental Design research design and the type taken is Non Equivalent Control Group Design. Research to know the effect of learning media macro flash 8 on student learning outcomes in terms of student motivation on thematic learning theme 7 SD N Mranggen 01. The subjects of this study were all students of grade IV of SDN Mranggen 01 Year Lesson 2017/2018. Samples taken are 25 students. Data from this research is obtained through observation, interview, test, questionnaire and documentation. The result of the research analysis showed that the classical percentage of UTS (76%) while on the classical classification posttest (92%), based on the correlation test results obtained r count> r table or 0.079> 0.396 so H0 rejected and Ha accepted. It can be concluded that there is a correlation between students' perceptions with media macroflash 8 on student learning outcomes in terms of student motivation on thematic learning theme 7 grade IV SD N Mranggen 01 and its influence of 20.17%. T test results obtained t count = 6.31. Thus H0 is rejected and Ha accepted. It can be concluded that there are differences in learning outcomes between students with high motivation and low motivation students on thematic learning theme 7 grade IV SDN Mranggen 01.Keywords: learning media macroflash 8, theme thematic theme 7 sub themes 1. AbstrakJenis Penelitian ini adalah penelitian kuantitatif dengan desain penelitian Quasi Eksperimental Design dan jenis yang diambil adalah Non-Equivalent Control Group Design. Penelitian ini bertujuan untuk mengetahui pengaruh media pembelajaran macroflash 8 terhadap hasil belajar siswa ditinjau dari motivasi siswa pada pembelajaran tematik tema 7 SD N Mranggen 01. Subyek penelitian ini adalah seluruh siswa kelas IV SDN Mranggen 01 Tahun Pelajaran 2017/2018. Sampel yang diambil adalah 25 siswa. Data dari penelitian ini diperoleh melalui observasi, wawancara, tes, angket dan dokumentasi. Hasil analisis penelitian menunjukan bahwa presentase klasikal UTS (76%) Sedangkan pada presentase klasikal posttest ( 92%), berdasarkan hasil uji korelasi diperoleh rhitung > rtabel atau 0,079 > 0,396 sehingga H0 ditolak dan Ha diterima. Dapat disimpulkan bahwa ada korelasi antara persepsi siswa dengan media macroflash 8 terhadap hasil belajar siswa ditinjau dari motivasi siswa pada pembelajaran tematik tema 7 kelas IV SD N Mranggen 01 dan pengaruhnya sebesar 20,17%. Hasil uji t diperoleh t hitung = 6,31. Selanjutnya thitung tersebut dibandingkan dengan ttabel = 2,06 dengan t1-1/2